Types And Clinical Features of Sevi/Karna Soolai (EAR ACHE) In Siddha Medicine - A Review - Thayalini, T.; Kavitha, T. (Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka, 2017)
Ear ache is one of the symptoms of Ear, Nose and Throat diseases. In Siddha Medicine it is consider as a disease under the Siroroga maruthuvam. Ear ache is described in many Siddha literatures in different ways. The aim of the study is to review the types and clinical features of Sevi Soolai in Siddha literatures. Five literatures were selected for this study. Sevi Soolai was mentioned in all five books. They are Pararajasekaram Siroroganithanam (6), Sarabenthira Vaithiya Muraikal Siroroga Nithanam (5), Siddhar Aruvai Maruthuvam (6), Yukimuni Vaithiya Sinthamani (5) and Thanvanthiri vaithiyam part - I. Data were listed out and analyzed. From the literature analysis ten types of Ear ache (Karna Soolai) were identified. Vatha, Pita and Kapha are mentioned in 40% of literatures. The signs and symptoms of Vatha, Pita and Kapha are able to compare to the clinical features of otitis externa (ear ache, tinnitus, deafness, scanty discharge), abscess in the external auditory tube (abscess, foul smell, Purulent blood stained discharge) and impacted wax (collection of wax, irritation and tinnitus) respectively. 60% literatures mentioned Kirumi, Rakta and Sanni Karna Soolai. The clinical features of Kirumi and Raktha Karna Soolai are compared to the clinical features of acute otitis media (ear ache, parulant discharge and deafness) and rupture of tympanic membrane due to trauma (bleeding) respectively. The clinical features of Sanni Karna Soolai (pain in the head, purulent discharge from the ear, swelling of the ear and deafness) are able to compare the clinical features of complication of middle ear infection. Neer, Vayu, Mankisa (muscle) and Sura Sevi Soolai are mentioned in 40% literatures. Ear ache is one of the symptoms of ear diseases in western medicine but in Siddha; it was classified based on the affected doshas
Keywords: Karna soolai; Ear ache; Siddha literature